2011
DOI: 10.1242/jcs.077065
|View full text |Cite
|
Sign up to set email alerts
|

A constraint network of interactions: protein–protein interaction analysis of the yeast type II phosphatase Ptc1p and its adaptor protein Nbp2p

Abstract: IntroductionInactivation of proteins that participate in more than one cellular process leads to a variety of apparently unconnected phenotypes. Understanding the molecular cause for each phenotype might reveal how seemingly independent cellular processes are regulated and coordinated in the cell. Genome-wide gene interaction data based on the simultaneous inactivation of more than one gene greatly facilitate this inherently complex analysis because genes with pleiotropic phenotypes often occupy central positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(81 citation statements)
references
References 53 publications
3
75
0
Order By: Relevance
“…Remarkably, only the mutation of Mkk1, one of the MAPKKs of the CWI pathway, was able to substantially suppress all the phenotypes of the ptc1 mutant tested in the screen (Figure 1 and Figure 2), as well as additional defects attributable to the ptc1 mutation (Figure 3 and Figure 4). This finding reinforces previous evidence linking Ptc1 to the CWI pathway (Huang and Symington 1995;Gonzalez et al 2006;Hruby et al 2011;Stanger et al 2012;SacristanReviriego et al 2015) and strongly suggests that abnormal activation of the CWI pathway is at the basis of many of the defects derived from the absence of Ptc1. It must be noted that an excessive activation of the CWI pathway can be deleterious, as observed when hyperactive alleles of Pkc1 or Mkk1 are overexpressed (Watanabe et al 1995;Martin et al 2000).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Remarkably, only the mutation of Mkk1, one of the MAPKKs of the CWI pathway, was able to substantially suppress all the phenotypes of the ptc1 mutant tested in the screen (Figure 1 and Figure 2), as well as additional defects attributable to the ptc1 mutation (Figure 3 and Figure 4). This finding reinforces previous evidence linking Ptc1 to the CWI pathway (Huang and Symington 1995;Gonzalez et al 2006;Hruby et al 2011;Stanger et al 2012;SacristanReviriego et al 2015) and strongly suggests that abnormal activation of the CWI pathway is at the basis of many of the defects derived from the absence of Ptc1. It must be noted that an excessive activation of the CWI pathway can be deleterious, as observed when hyperactive alleles of Pkc1 or Mkk1 are overexpressed (Watanabe et al 1995;Martin et al 2000).…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Figure 5B, overexpression of Ptc1 was able to reduce the strong Slt2 phosphorylation promoted by Bck1 CT . Because this version does not contain the N-terminal Nbp2-binding proline-rich motif (Hruby et al 2011), we previously confirmed that Nbp2 is not necessary for overexpressed Ptc1 to act on the CWI pathway ( Figure S2). Bck1 CT also lacks the phosphorylation sites necessary for its activation by Pkc1 (Levin et al 1994).…”
Section: Ptc1 Reduces Cwi Signaling By Acting At the Mapkk Levelmentioning
confidence: 61%
See 1 more Smart Citation
“…3A,B) (Hruby et al, 2011;Labedzka et al, 2012). Deleting 229 or 529 residues from the C-terminus of Myo1p (Myo1 1-1700 , Myo1 1-1400 ) hardly affected the interaction with Bni5p whereas a Myo1-fragment covering only the N-terminal 1100 residues displayed only very weak binding (Fig.…”
Section: Bni5p Induces Myo1p Higher-order Structuresmentioning
confidence: 97%
“…Analysis of the ptc1⌬ mutant using DNA microarrays showed no significant effects on expression of glucoseregulated genes (21,22). Ptc1 binds to the adaptor protein Nbp2, which mediates its association with multiple protein kinases, but SNF1 was not identified as an interaction partner (23). We here examine the effects of the ptc1⌬ mutation and Ptc1 overexpression, in combination with reg1⌬ and/or sit4⌬ mutations, on Thr-210 phosphorylation of wild-type and mutant forms of SNF1.…”
mentioning
confidence: 99%